2017
DOI: 10.1016/j.bbalip.2017.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoglycerol dihydroceramide, a distinctive ceramide produced by Porphyromonas gingivalis, promotes RANKL-induced osteoclastogenesis by acting on non-muscle myosin II-A (Myh9), an osteoclast cell fusion regulatory factor

Abstract: Among several virulence factors produced by the periodontal pathogen Porphyromonas gingivalis (Pg), a recently identified novel class of dihydroceramide lipids that contains a long acyl-chain has the potential to play a pathogenic role in periodontitis because of its higher level of tissue penetration compared to other lipid classes produced by Pg. However, the possible impact of Pg ceramides on osteoclastogenesis is largely unknown. In the present study, we report that the phosphoglycerol dihydroceramide (PGD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 66 publications
0
36
0
Order By: Relevance
“…These results suggest that high levels of Myo2a inhibit osteoclast fusion, and that its loss triggers the fusion process. Other studies have confirmed these findings [51,52] and have likewise shown that reducing myosin II activity by inhibition of myosin light chain kinase similarly triggers osteoclast fusion [53]. Precisely how Myo2a achieves this inhibition is unclear, but it may be due to production of intracellular tension at defined locations within the cells.…”
Section: Class II Myosinsmentioning
confidence: 78%
“…These results suggest that high levels of Myo2a inhibit osteoclast fusion, and that its loss triggers the fusion process. Other studies have confirmed these findings [51,52] and have likewise shown that reducing myosin II activity by inhibition of myosin light chain kinase similarly triggers osteoclast fusion [53]. Precisely how Myo2a achieves this inhibition is unclear, but it may be due to production of intracellular tension at defined locations within the cells.…”
Section: Class II Myosinsmentioning
confidence: 78%
“…P. gingivalis factors promote bone resorption [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. In this study, bone resorption was evaluated along the socket of the third molar; the resorption provoked by P. gingivalis infection added to the physiological osteoclastic resorption related to the physiological tooth drift [37] .…”
Section: Discussionmentioning
confidence: 99%
“…Kanzaki et al have reported that phosphoglycerol dihydroceramide (PGDHC), a ceramide produced by the peridontal pathogen Porphyromonas gingivalis , is the virulence factor promoting the formation of larger osteoclasts. PGDHC directly binds to non-muscle myosin IIA (Myh9), elevating the expression of DC-STAMP by activating Rac1 GTPase [ 195 ].…”
Section: Recent Pre-clinical Studiesmentioning
confidence: 99%